A randomized, blinded, placebo-controlled trial comparing antibody responses to homeopathic and conventional vaccines in university students. Issue 48 (19th November 2018) - Loeb, Mark; Russell, Margaret L.; Neupane, Binod; Thanabalan, Vitheya; Singh, Pardeep; Newton, Jennifer; Pullenayegum, Eleanor
Highlights: Homeopathic vaccines failed to elicit an antibody response. The antibody response to homeopathic vaccines was similar to placebo. In contrast, conventional vaccines showed a robust response. These findings suggest homeopathic vaccines should not be licensed. Abstract: Background: Homeopathic vaccines are licensed in many countries but scientific data to support their use are sparse. The goal of this study was to compare the antibody response of homeopathic and conventional vaccines and placebo in young adults. We hypothesized that there would be no significant difference between homeopathic vaccines and placebo, while there would be a significant increase in antibodies in those received conventional vaccines. Methods: A randomized blinded placebo-controlled trial was conducted where 150 university students who had received childhood vaccinations were assigned to diphtheria, pertussis, tetanus, mumps, measles homeopathic vaccine, placebo, or conventional diphtheria, pertussis, tetanus (Tdap) and mumps, measles, rubella (MMR) vaccines. The primary outcome was a ≥ two-fold increase in antibodies from baseline following vaccination as measured by ELISA. Participants, investigators, study coordinator, data blood drawers, laboratory technician, and data analyst were blinded. Results: None of the participants in either the homeopathic vaccine or the placebo group showed a ≥ two-fold response to any of the antigens. In contrast, of those vaccinated with Tdap, 68% (33/48) had a ≥ two-fold response to diphtheria, 83% (40/48) to pertussis toxoid, 88% (42/48) to tetanus, and 35% (17/48) of those vaccinated with MMR had a response to measles or mumps antigens (p < 0.001 for each comparison of conventional vaccine to homeopathic vaccine or to placebo). There was a significant increase in geometric mean titres of antibody from baseline for conventional vaccine antigens (p < 0.001 for each), but none for the response to homeopathic antigens or placebo. Conclusions: Homeopathic vaccines do not evoke antibody responses and produce a response that is similar to placebo. In contrast, conventional vaccines provide a robust antibody response in the majority of those vaccinated. Trial Registry: NCT 02825368 .